Nursing students' self-directed learning abilities and related factors at graduation: A multi-country cross-sectional study - Visiers-Jiménez, Laura; Palese, Alvisa; Brugnolli, Anna; Cadorin, Lucia; Salminen, Leena; Leino-Kilpi, Helena; Löyttyniemi, Eliisa; Nemcová, Jana; Simão de Oliveira, Célia; Rua, Marília; Zeleníková, Renáta; Kajander-Unkuri, Satu; et al. (Nursing open, 2022)
AIM: To describe nursing students' level of self-directed learning abilities and identify possible factors related to it at graduation in six European countries. DESIGN: A cross-sectional comparative design across the countries. METHODS: The study was conducted from February 2018 to September 2019. Nursing students (N = 4,135) from the Czech Republic, Finland, Italy, Portugal, Slovakia and Spain were invited to respond to the research instruments (the Self-Rating Scale of Self-Directed Learning and the Nurse Competence Scale) at graduation. The data were analysed using the chi-square test, Pearson correlation coefficient and the linear model. RESULTS: The nursing students' (N = 1,746) overall self-directed learning abilities were at high level in all countries. Statistically significant differences occurred between countries. Spanish nursing students reported the highest level of self-directed learning abilities while students from the Czech Republic reported the lowest. Higher level of self-directed learning abilities was related to several factors, particularly with the self-assessed level of competence and country.
Keywords: Learning; inteligence; lidé; studenti ošetřovatelství; Europe; nursing education; Evropa; Cross-Sectional Studies; Students, Nursing; competence; self-directed learning; učení; Intelligence; graduating nursing student; průřezové studie; Humans